Idarubicin-loaded ONCOZENE® drug-eluting bead chemoembolization in a rabbit liver tumor model: investigating safety, therapeutic efficacy and effects on tumor microenvironment - Borde, Tabea (J Vasc Interv Radiol, 2020)
PURPOSE: To investigate toxicity, efficacy, and microenvironmental effects of idarubicin-loaded 40μm and 100μm drug-eluting embolic transarterial chemoembolization (DEE-TACE) in a rabbit liver tumor model. MATERIALS AND METHODS: 12 male New-Zealand White rabbits with orthotopically implanted VX2 liver tumors were assigned to DEE-TACE with 40μm (n=5) or 100μm (n=4) Oncozene® microspheres or as untreated controls (n=3). 24–72h post-procedurally, multi-parametric MRI (mpMRI) including dynamic contrast-enhanced (DCE), diffusion-weighted imaging (DWI), and biosensor imaging of redundant deviation in shifts (BIRDS) assessing extracellular pH (pH(e)), was performed, followed by immediate sacrifice. Laboratory parameters and histopathological ex-vivo analysis included fluorescence confocal microscopy and immunehistochemistry. RESULTS: DCE-MRI demonstrated a similar degree of devascularization of embolized tumors for both microsphere sizes (mean arterial enhancement [%] 8±12 vs. controls 36±51, p=.07). Similarly, DWI showed post-procedural increases in diffusion across the entire lesion (apparent diffusion coefficient [x10–3mm2/s] 1.89±0.18 vs. liver 2.34±0.18, p=.002). BIRDS demonstrated profound tumor acidosis at baseline (mean pH(e) tumor 6.79±0.08 vs. liver 7.13±0.08, p=.02), and after DEE-TACE (tumor 6.8±0.06 vs. liver 7.1±0.04, p=.007). Laboratory and ex-vivo analyses showed central tumor core penetration, and greater increase in liver enzymes for 40μm as compared to 100μm microspheres. Inhibition of cell proliferation, intra-tumoral hypoxia, and limited idarubicin elution were equally observed in both spheres. CONCLUSIONS: Non-invasive MpMRI visualized chemoembolic effects on the tumor and tumor microenvironment following DEE-TACE. Devascularization, increased hypoxia, coagulative necrosis, tumor acidosis, and limited idarubicin elution suggest ischemia as the predominant therapeutic mechanism. Substantial size-dependent differences indicate a greater toxicity of the smaller microsphere diameter.